Adaptation to Portuguese of the short version of the Supervisory Relationship Questionnaire - Nogueira, Rita Santos (2019)
The main objective of this study was the adaptation to Portuguese of a questionnaire of supervisory relationship – short version of the Supervisory Relationship Questionnaire (supervisee version). The lack of national measures on this construct and its importance to the satisfaction with the supervision, development of the trainee and to the effectiveness of supervision motivated this investigation. Ninety clinical psychologists/psychotherapists in supervision were recruited. To adapt this questionnaire we made a translation, a retroversion, a pretest. The participants also completed the Short-scale Eysenck Personality Questionnaire Revised (adaptation Almiro & Simões, 2013) to ascertain divergent validity and the CASES (adaptation Lamares & Conceição, 2012) to determine the predictive validity. A small adjustment was made, in the confirmatory factorial analysis. The results show a measure composed of 17 items divided by the same three subscales of the original measure. Adequate psychometric properties (internal consistency, factorial validity and divergent validity) have been demonstrated. The utility and practical application of this measure and suggestions for future research are discussed.